Getting Bigger by Growing Smaller: A New Growth Model for Corporate America - Shulman, Joel; Stallkamp, Thomas (Financial Times Prentice Hall books., 2003)
Large, mature companies always become trapped at some point in the declining stages of what has become known as the corporate life cycle. Historically this barrier to continued growth has been, and is still, as unavoidable as death and taxes. In Getting Bigger by Growing Smaller, Joel Shulman, a leading researcher on entrepreneurship, teams up with Thomas T. Stallkamp, one of the world's most effective executives, to introduce a powerful new growth model for corporate America (based on 4 years of research at Babson College and Harvard University) that can enable corporations to break through this barrier to growth by utilizing a new breakthrough business model called the Strategic Entrepreneurial Unit (SEU). Shulman and Stallkamp demonstrate how to build new employee/entrepreneur-led startups within the corporation--entities that can take on new market opportunities and deliver startup-level growth. This is the first book to provide practical methods for actually identifying, creating, and implementing smaller units within large organizations to enable continued, rapid growth beyond the predictable barriers of the corporate life cycle.